Tendências temporais do câncer infantojuvenil e fatores associados ao tratamento oncológico : análise a partir dos Registros Hospitalares de Câncer no Brasil - Lucena, Nyellisonn Nando Nóbrega de (2022)
Cancer and its monitoring should be considered a priority in all countries, regardless of their development status. In Brazil, monitoring of cases is based on systematized information on morbidity and mortality made available by the Population-Based Cancer Registries (RCBP), Hospital Cancer Registries (RHC) and the Mortality Information System (SIM), which help in the epidemiological description. of cancer. The present study aimed to analyze temporal trends in the prevalence rate of childhood cancer and factors associated with cancer treatment, from 2000 to 2018, based on the regional and national investigation of Hospital Cancer Registries. This is an observational, retrospective, secondary-based study with a quantitative approach. The sample consisted of 81,395 cancer records contained in the Integrating Module of Hospital Cancer Records of the Instituto Nacional de Câncer José Alencar Gomes da Silva (INCA) and made available by the Fundação Oncocentro de São Paulo (FOSP), with information from children and adolescents from 0 to 19 years old, treated in specialized centers and units. Data were analyzed descriptively and through inferential analysis, where Joinpoint regressions and logistic regression were performed, adopting a significance level of 5%. Childhood cancer, in Brazil, from 2000 to 2018, was more prevalent in males (54.2%; n=44,103), in children between 0 and 4 years of age (31.2%; n= 25,428), in brown-skinned individuals (40.8%; n=22,839), and residents of the Southeast region (44.9%; n= 36,522). Regarding the classification of diagnosis, the most relevant was that of Leukemias, myeloproliferative diseases and myelodysplastic diseases (28.8%; n= 23,416). Solid tumors predominated in these individuals (58.7%; n= 47,780). Pediatric Oncology was the specialty that most treats this disease (34.6%, n= 19,346) and chemotherapy was the most administered therapeutic modality at the beginning of treatment (48.1%; n= 26,935). It was noticed that 78.1% (n=63,571) of the individuals started the treatment up to 60 days after the diagnosis was confirmed. Regarding regional differences, individuals from the Midwest region used SUS referrals more (81.2%) and underwent anticancer treatment in other states (32.7%). The North region had the highest percentage of deaths after the first hospital treatment (17.4%). A significant increase in prevalence rates was observed over time, especially in solid tumors, in males and in the age group 0-4 years, with variations between Brazilian regions. Patients whose first hospital treatment was radiotherapy (OR: 3.74; 95% CI: 2.9381; 4.7891), hormone therapy (OR: 8.24; 95% CI: 2.6896; 24.0811) and bone marrow transplantation (OR: 15.7 ; 95%CI: 3.9650; 75.1479), and who arrived at specialized centers with diagnosis and without treatment (OR: 11.4; 95%CI: 9.8555; 13.2940) and with diagnosis and treatment (OR: 56.2; 95%CI: 45.7427 ; 69.3543) were more likely to delay the start of cancer treatment. It is concluded that the leukemia group was the most predominant among children and adolescents with cancer, affecting mainly children aged 0 to 4 years old and males. Most patients started treatment within the period determined by law and the increase in the prevalence rate was more evident for solid tumors, in males and in the age group from 0 to 4 years, varying between Brazilian regions. The study was able to predict a model with promising efficacy for classifying possible children and adolescents who may delay the start of anticancer treatment.